THE CONTRIBUTIONS OF IMPACT FACTOR PUBLICATION POLICY TO ACADEMIC DEVELOPMENT IN NIGERIAN HIGHER INSTITUTIONS OF LEARNING: A CRITICAL EVALUATION - Chukwuemeka, Eze Malachy; Chekwubechukwu, Obidigbo Godwin; Obuteaku, Nwobi Fidelia (International Journal of Research -GRANTHAALAYAH, 2018)
Motivation/Background: Publishing in highly rated journals has being the primary prerequisite for hiring, appraising and promoting academics in higher institutions since the beginning of the 21st century. Lecturers became concerned more with this than classroom activities. This paper seeks answers to the following questions: what is the nature of impact factor publishing? Is there any relationship between impact factor policy and the development of education and scholarship in Nigerian higher institutions? Methods: Qualitative data gathering, content analysis, and Conservative Theory of imperialism as framework of analysis were adopted. Results: The results reveal that impact factor is an ineffective index for academic evaluation, perpetuates academic and economic imperialism, and undermines the development of higher education and scholarship in Nigeria. Conclusions: The mechanisms of impact factor rating are entirely western and neo-colonial, while its application as measurement index for evaluation of lecturers negates the goal for which it was introduced. The relevance of this conclusion for higher education in Nigeria lies in its advocacy for policy reforms and the abrogation of orthodox impact factor policy. Thess supports the recommendations of some scholars for the re-introduction of orthodox classroom performance evaluation index that has been discarded for the policy.